(3MOGFb GdCfhGQ GdRGgQI hYbhO GdOQQ GdaGNQIs - (3MSjf Hf eUWaj GdJQLeGfs
(3ChdgG (B:s
(3MeOG def LYd GdCOH PNjQI GaJNQ HGbJfGFgG GdeaJNQhf, hai GbJfGU ThGQOg GdYQjVI JfGaS GdeJfGaShf s
(3BNQgG (B:s
(3hJLYd GdQbYI GdecJhHI ajgG GdOYGA GdePchQ ai bUHI hjSO bGYgG SOG eMceG hJVY GdbUHI ceG PcQfG GfJgi s
(3GdLRA GdKGfi efgG HQbe (B26/ (3chjJs
(3GdfSNI HgG MhGTs
(3HChd GdeNWhW agQSJs
(3HUaMI GdYfhGf EgOGA s
(3HgG LOGhd JhVjMjIs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs